Revitalizing Outbound Creative Village Based on Place Attachment - Prahmita Karima; D. Lindarto (International Journal of Architecture and Urbanism, 2022)
Creative Village is a rural outbound camp area that has a traditional concept. The traditional games in this area are playing kites, jumping rope, marbles, stilts, Sodor carts, bezel balls, shadow puppets, and so on. This tourist area is located in the countryside, away from highways and noise. This study aims to revitalize the area so that its utilization can be more optimal. The method used is qualitative, namely direct observation in the research area. The phenomenon in the area has not been fully utilized in terms of its potential. The conditions that occur are things that are considered potentially unused. The revitalization area uses the Place Attachment theory as the basis, the theory of outdoor design as a reflection of the needs of the tourist area, and Kevin Lynch's theory will be used to determine what is considered attractive and has the potential to be developed or eliminated. This result was obtained from the revitalization of the area as a tourism village and tourism object in the Deli Serdang Regency.